Flat planting of cassava is more productive, economic and labour-saving than in annual ridges in the high-rainfall environments of Northern Zambia - Kamaluddin Tijjani Aliyu; Kalala, Kelvin; Simutowe, Esau; MacLaren, Chloe; Mhlanga, Blessing; Ngoma, Hambulo; Silva, João Vasco; Thierfelder, Christian (Elsevier, 2026)
Context: Cassava (Manihot esculenta Crantz) is a strategic crop for food and income generation, but its productivity is challenged by low soil fertility, poor agronomic practices, and variable environmental conditions. Conservation Agriculture (CA) has been proposed as a sustainable intensification strategy, but its effectiveness in cassava-based systems has not been researched in Zambia, particularly when intercropped with legumes. Objectives: This study evaluated cassava-legume cropping systems' agronomic, nutritional, and economic performance under CA and conventional practice (CP) in high rainfall conditions. Using an on-farm mother-and-baby trial setup, six cropping systems - combining tillage practices and legume intercrops (common bean and groundnut) were assessed for root yield, legume grain yield, energy and protein contributions, and net economic returns. Methods: Two cassava cropping systems, flat planting as CA and planting on annual ridges as CP, were evaluated in a multi-location on-farm trial. Each cropping system was tested with two intercrop legumes and as sole cassava, across four consecutive cropping seasons. A cluster analysis was used to classify the experimental fields into three yield potential clusters. The cropping system treatments in each cluster were assessed using the Sustainable Intensification Assessment Framework (SIAF), with metrics representing productive, economic and human dimensions. Results and conclusions: Results showed that planting cassava on the flat, especially when intercropped with legumes under conservation agriculture (CA_Bn and CA_Gn), did not compromise cassava yield and significantly enhanced legume grain, protein, and energy yields. These benefits were more pronounced in high and medium yielding environments. Economic analyses revealed higher net benefits and return to inputs in flat-planted intercrops, though labour costs were also higher. Labour productivity varied across clusters, influencing the suitability of systems under local constraints. Significance: Overall, planting cassava in flat offers a promising strategy for intensifying cassava production, improving food security, and enhancing profitability for smallholder farmers in Northern Zambia.